2020
DOI: 10.1021/acs.inorgchem.0c00458
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Modulation of Pd-Based Bimetallic Catalysts with Sulfur-Doped Carbon Support for Phenylacetylene Semihydrogenation

Abstract: The semihydrogenation of phenylacetylene to styrene represents an important process for optimizing the polystyrene production and also a model reaction for the evaluation of selective hydrogenation catalysts. Although the alloying strategy and surface engineering for noble metal (particularly for Pd) catalysts can effectively inhibit the overhydrogenation of styrene, the selectivity of phenylacetylene semihydrogenation to styrene is generally below 95% near the full conversion. Here, we demonstrate the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Different from the conventional perception that sulfur was poisonous to noble metal, recent studies indicated that S-doped carbon may be a promising support for noble-metal catalysts. Chen et al investigated the ORR performance and durability of S-doped graphene-supported Pt nanoparticles . The negative shift of S 2p binding energy strongly manifested the electrons transferred from Pt nanoparticles to the S-doped graphene support.…”
Section: The Influence Of Carbon Properties On Emsimentioning
confidence: 99%
“…Different from the conventional perception that sulfur was poisonous to noble metal, recent studies indicated that S-doped carbon may be a promising support for noble-metal catalysts. Chen et al investigated the ORR performance and durability of S-doped graphene-supported Pt nanoparticles . The negative shift of S 2p binding energy strongly manifested the electrons transferred from Pt nanoparticles to the S-doped graphene support.…”
Section: The Influence Of Carbon Properties On Emsimentioning
confidence: 99%
“…Selective catalytic hydrogenation among various catalytic processes is a kind of important reaction, as it produces high-value chemicals through the control of the hydrogenation degree of a low-value reactant. The process of phenylacetylene semihydrogenation is of great significance because phenylacetylene is considered to be a harmful feedstock for polystyrene industrial production in the polymerization process of styrene. Therefore, it is desired to achieve a high selectivity of styrene while keeping a high conversion of phenylacetylene during the reaction process. It is generally accepted that palladium catalysts are mostly used to achieve a high catalytic performance for this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the excellent atomic dispersion of as‐prepared Pd 1 /BP SACs (0.3 wt%, 0.6 wt%, 1.5 wt%) results in a reasonably high turnover frequency (TOF) of 0.3 s −1 in the semi‐hydrogenations of 3‐butynylbenzene (Table S2, Supporting Information). [ 43–50 ] It is worth mentioning that little aggregated Pd atoms in Pd 1 /BP after the hydrogenation reactions suggest atomic dispersion of single metal atoms on BP can be maintained (Figure S30, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%